Teachers’ and Students’ Assessment of the Influence of School Rooms Acoustic Treatment on Their Performance and Wellbeing - POLEWCZYK, Irena; JAROSZ, Mikołaj (Archives of Acoustics, 2020)
The paper presents the latest research results concerning the correlation between changes in the room acoustics of school spaces and noticeable changes in the communication and functioning of students and teachers at school. The primary school covered by the research is the second largest school of this type in Poland. The large number of students and hard interior finishing made the acoustic conditions in the school building very unfavourable. The measurements showed that school rooms were very noisy and reverberant. The measured values of reverberation time T were in many rooms 3–4 times higher than the acceptable values specified in the mandatory Polish acoustic standard PN-B-02151-4:2015-06. Also the speech intelligibility measured by the speech transmission index was very poor, in the extreme case STI = 0:31. This situation (very characteristic for most of Polish schools) became the basis for the first such comprehensive acoustic treatment of the whole school building in Poland. This intervention allowed to meet PN-B-02151-4:2015-06 demands almost in every room accessible for students. This case gave an excellent opportunity to assess the influence of improved room acoustics on teachers’ and students’ performance and wellbeing. Measurements of the equivalent sound level LAeq, reverberation time T and STI speech transmission index were made before and after acoustic treatment. The questionnaire survey used the Acoustic Change Feelings Scale (ACFS-S, ACFS-T) for teachers and students. 378 students, and 44 teachers were included in the study. Both students’ and teachers’ answers show significant improvement of their performance and wellbeing. Positive changes were noticed in students’ level of concentration, short memory capacity and pace of work. After acoustic treatment students (both in teachers’ and their own opinion) can better hear and understand teachers’ instructions and are much more capable of task fulfilling. Both teachers and students observed clear reduction of aggression level. Teachers reported considerable drop in students’ fatigue and their own voice effort.